Peran Konselor Dalam Membina Kepribadian Narapidana Penyalahgunaan Narkoba Dilapas Perempuan Kelas II A Palembang - Yanti, Juni; Razzaq, Abdur; Fitri, Hartika Utami (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
This research is entitled "The Role of Counselors in Building the Personality of Drug Abuse Convicts in the Class II A Palembang Women's Prison". A counselor is a person who has expertise in the field of counseling services, he is a professional. This counselor also trains drug abuse convicts. Drug abuse is drug use that is not done for the purpose of treatment, but because they want to enjoy its effects. Because of its influence, many drugs are abused. The aim of this research is to analyze the role of counselors in developing the personality of drug abuse prisoners in the Class II A Palembang women's correctional institution and to analyze the counselor's obstacles in developing the personality of drug abuse prisoners in the Class II A Palembang women's correctional institution. This type of research is field research using a qualitative approach with descriptive research methods. The data collection tools used in this research are observation, interviews and documentation. The data analysis techniques in this research are data reduction, data modeling or data presentation and drawing conclusions. The subjects of this research were the counselor and client "A". The results of this research show that the role of counselors in developing the personality of drug abuse convicts is to provide guidance to drug addict inmates by carrying out a counseling process for drug addict inmates up to the recovery stage, namely by carrying out medical and social rehabilitation. The aim of this personality development is so that when inmates in correctional institutions are free from punishment, they can be accepted again by society and their environment and can live normally as before. The obstacle for counselors in developing the personality of drug abuse inmates is that drug addict inmates are not yet aware of the purpose of this personality developmentployees.